The Implementation of the Qiraati Method in Early Childhood Education: A Case Study of Teacher Mentoring in Addressing Learning Challenges in the PRA PTPT Class at TPQ Sunan Kalijogo, Poncokusumo - Zuhriyyah Al-‘Adaniy; Muhammad Odik Arifin (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
Advanced Qur'an learning for early childhood is often criticized for triggering academic anxiety. This qualitative case study aims of dissect the transition curriculum management of the Pra Program Tahfidz Pasca TPQ (PRA PTPT) based on the Qiraati Method at TPQ Sunan Kalijogo Poncokusumo Malang, and explore teacher strategies and institutional policies in overcoming toddlers' behavioral problems, phonological articulation barriers (lisping), and spiritual strengthening. Data were collected through participant observation, documentation, and in depth interviews with five key informants. The results show that the transition curriculum implements a rigid binadzor reading speed leveling system (Levels 1–5) based on an accumulative repetition pattern. The curriculum rigidity is balanced by flexible yet firm teacher strategies through distraction redirecting tactics, inclusive-persuasive approaches, the policy of single-teacher continuity, bureaucratic clinical supervision synergy, and the support of collective spiritual pathways (tirakat). Lisping barriers are clinically resolved using intensive audio-visual imitation methods. The implication proves that accelerating high-level Qur'anic literacy during the golden age can be optimally achieved without disrupting child psychology through a structured methodological ecosystem, adaptive policy synergy, and consistent spiritual approaches.